2018
DOI: 10.1177/1744806918757286
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of neutrophils and interleukin-18 in nociception in a mouse model of muscle pain

Abstract: Muscle pain is a common condition that relates to various pathologies. Muscle overuse induces muscle pain, and neutrophils are key players in pain production. Neutrophils also play a central role in chronic pain by secreting interleukin (IL)-18. The aim of this study was to investigate the involvement of neutrophils and IL-18 in a mouse model of muscle pain. The right hind leg muscles of BALB/c mice were stimulated electrically to induce excessive muscle contraction. The left hind leg muscles were not stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
(91 reference statements)
2
24
0
Order By: Relevance
“…However, excessive PMN responses may contribute to ongoing inflammation and tissue damage in a number of diseases and ailments [32,33,34,35]. Compelling evidence supports the use of cannabis and CBD in a plethora of pathological conditions, some of which stem from the exacerbation of the inflammatory response of PMN and include pain [36], multiple sclerosis [37], diabetic complications [38], inflammatory bowel disease [39], cardiovascular diseases [40], hypoxia-ischemia injury [41], rheumatoid arthritis [35], cancer [42], and Crohn’s disease [43]. Collectively, our findings point to PMN as potential targets for the therapeutic actions of cannabis and CBD.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive PMN responses may contribute to ongoing inflammation and tissue damage in a number of diseases and ailments [32,33,34,35]. Compelling evidence supports the use of cannabis and CBD in a plethora of pathological conditions, some of which stem from the exacerbation of the inflammatory response of PMN and include pain [36], multiple sclerosis [37], diabetic complications [38], inflammatory bowel disease [39], cardiovascular diseases [40], hypoxia-ischemia injury [41], rheumatoid arthritis [35], cancer [42], and Crohn’s disease [43]. Collectively, our findings point to PMN as potential targets for the therapeutic actions of cannabis and CBD.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, we previously reported that IL-18 is secreted from neutrophils using a muscle pain model. 9…”
Section: Introductionmentioning
confidence: 99%
“…For example, the present study demonstrated, for the first time, the involvement of P2X3 receptors in neutrophil migration induced by static contraction. It is well known that neutrophils have a role on different pain conditions [16,17,65,67], including muscle pain [11,30,33,68,69]. Neutrophils invade skeletal muscles and are assumed to produce pro-inflammatory cytokines after exercise-induced muscle damage [70].…”
Section: Discussionmentioning
confidence: 99%